Nurses’ spirituality and resilience during the month of Ramadan - Sevinc, Sibel; Serap Ozdemir, (Journal of the Pakistan Medical Association, 2023)
Objective: To examine the relationship between spirituality and resilience among nurses during Ramadan. Method: The cross-sectional, descriptive study was conducted at a state hospital in Turkey in May and June 2019, which coincided with the fasting month of Ramadan. The sample comprised nurses of either gender. Data was collected using a socio-demographic instrument, the Spirituality and Spiritual Care Rating Scale and the Resilience in Midlife Scale. Data was analysed using SPSS 24. Results: Of the 207 nurses, 145(70%) were female and 62(30) were male. Most of the nurses were aged 25-29 years 88(42.5%). Also, 86(41.5%) were married and 167(80.7%) had university education. Age affected religiosity (p=0.038), and there was a positive correlation of resilience with the spiritual care subscale and the spirituality total score (p<0.05). Besides, education status affected resilience (p=0.042). Conclusions: In order to increase spirituality among nurses, information should be provided during their education and training programmes about the importance of spirituality. Key Words: Spirituality, Resilience, Religion, Nurses.